Fact-Checking Interventions as Counteroffensives to Disinformation Growth: Standards, Values, and Practices in Latin America and Spain - Moreno-Gil, Victoria (2021)
As democracy-building tools, fact-checking platforms serve as critical interventions in the fight against disinformation and polarization in the public sphere. The Duke Reporters’ Lab notes that there are 290 active fact-checking sites in 83 countries, including a wide range of initiatives in Latin America and Spain. These regions share major challenges such as limited journalistic autonomy, difficulties of accessing public data, politicization of the media, and the growing impact of disinformation. This research expands upon the findings presented in previous literature to gain further insight into the standards, values, and underlying practices embedded in Spanish and Latin American projects while identifying the specific challenges that these organizations face. In-depth interviews were conducted with decision-makers of the following independent platforms: Chequeado (Argentina), UYCheck (Uruguay), Maldita.es and Newtral (Spain), Fact Checking (Chile), Agência Lupa (Brazil), Ecuador Chequea (Ecuador), and ColombiaCheck (Colombia). This qualitative approach offers nuanced data on the volume and frequency of checks, procedures, dissemination tactics, and the perceived role of the public. Despite relying on small teams, the examined outlets’ capacity to verify facts is noteworthy. Inspired by best practices in the US and Europe and the model established by Chequeado, all the sites considered employ robust methodologies while leveraging the power of digital tools and audience participation. Interviewees identified three core challenges in fact-checking practice: difficulties in accessing public data, limited resources, and the need to reach wider audiences. Starting from these results, the article discusses the ways in which fact-checking operations could be strengthened.